Experimental seismic performance evaluation of brick masonry cavity-wall buildings. (July 2022) - Ullah Khan, Sifat; Naseer, Amjad; Fahim, Muhammad; Ashraf, Mohammad; Badshah, Eid
Abstract: A full-scale single room cavity-wall brick masonry structure is tested under quasi-static reverse cyclic loading to evaluate its seismic behavior at the Earthquake Engineering Center, University of Engineering and Technology in Peshawar, Pakistan. The materials and techniques used in the specimen are typical of those found in the northern areas of Pakistan affected by the Kashmir earthquake of 2005. The results are presented in the form of force-deformation hysteresis loops and envelope curves. The three performance levels, namely immediate occupancy (IO), life safety (LS), and collapse prevention (CP) have been established. They correspond to story drift levels of 0.031%, 0.448%, and 0.600% respectively. Careful observation of the damage mechanism revealed the structure behaved predominantly in a flexure rocking mode.